Deep palaeoproteomic profiling of archaeological human brains. - Alexandra Morton-Hayward; Sarah Flannery; Iolanda Vendrell; Roman Fischer (PLoS ONE)
Palaeoproteomics leverages the persistence, diversity, and biological import of ancient proteins to explore the past, and answer fundamental questions about phylogeny, environment, diet, and disease. These insights are largely gleaned from hard tissues like bone and teeth, as well-established protocols exist for extracting ancient proteins from mineralised tissues. No such method, however, exists for the soft tissues, which are underexplored in palaeoproteomics given permission for destructive analysis routinely depends on a proven methodology. Considering less than one-tenth of all human proteins are expressed in bone, compared to three-quarters in the internal organs, the amount of biological information presently inaccessible is substantial. We address this omission with an optimised LC-FAIMS-MS/MS workflow yielding the largest, most diverse palaeoproteome yet described. Using archaeological human brains, we test ten protocols with varied chemistries and find that urea lysis effectively disrupts preserved membrane regions to expose low-abundant, intracellular analytes. Further, we show that ion mobility spectrometry improves unique protein identification by as much as 40%, and represents a means of "cleaning" dirty archaeological samples. Our methodology will be useful for improving protein recovery from a range of ancient tissues and depositional environments.